2021
DOI: 10.3390/cancers13143617
|View full text |Cite
|
Sign up to set email alerts
|

An Update on Hepatocellular Carcinoma in Chronic Kidney Disease

Abstract: Chronic kidney disease is a major public health issue globally and the risk of cancer (including HCC) is greater in patients on long-term dialysis and kidney transplant compared with the general population. According to an international study on 831,804 patients on long-term dialysis, the standardized incidence ratio for liver cancer was 1.2 (95% CI, 1.0–1.4) and 1.5 (95% CI, 1.3–1.7) in European and USA cohorts, respectively. It appears that important predictors of HCC in dialysis population are hepatotropic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…These groups mainly include health care providers, illicit injected drug users, sexually active individuals (more than 1 partner in the past 6 mo), persons with diabetes, dialysis patients, and people living with human immunodeficiency virus (HIV). The last two groups, in addition to showing a higher risk of HBV infection compared to the general population[ 68 - 70 ] due to the frequent use of percutaneous materials and the common route of HBV and HIV transmission, have shown suboptimal responses to HBV immunization[ 71 , 72 ]. Patients on dialysis have also shown a diminished response to the HBV vaccine probably due to a uremic-associated suppression of the immune system that leads to a significant progressive reduction of the percentage and count of lymphocytes CD3+, CD4+, and CD8+ and a disturbance of antigen-presenting cells that results in an inability to sustain a satisfactory antibody titer over time[ 73 - 76 ].…”
Section: Management Of Special Populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These groups mainly include health care providers, illicit injected drug users, sexually active individuals (more than 1 partner in the past 6 mo), persons with diabetes, dialysis patients, and people living with human immunodeficiency virus (HIV). The last two groups, in addition to showing a higher risk of HBV infection compared to the general population[ 68 - 70 ] due to the frequent use of percutaneous materials and the common route of HBV and HIV transmission, have shown suboptimal responses to HBV immunization[ 71 , 72 ]. Patients on dialysis have also shown a diminished response to the HBV vaccine probably due to a uremic-associated suppression of the immune system that leads to a significant progressive reduction of the percentage and count of lymphocytes CD3+, CD4+, and CD8+ and a disturbance of antigen-presenting cells that results in an inability to sustain a satisfactory antibody titer over time[ 73 - 76 ].…”
Section: Management Of Special Populationsmentioning
confidence: 99%
“…Consequently, for patients on dialysis and/or living with HIV, other approaches are recommended to enhance the HBV vaccine immune response. For patients undergoing dialysis therapy, alternative strategies include the use of adjuvants, additional vaccination cycles, different vaccine formulations, greater number and concentration of doses, greater frequency of doses, dual vaccination, alternative administration routes, and/or use of booster vaccines[ 67 , 72 , 84 - 86 ]. On the other hand, for HIV-infected individuals with negative or < 10 mIU/mL anti-HBs levels after a primary vaccine series, a second HBV vaccine series using larger or additional doses is recommended[ 71 , 87 ].…”
Section: Management Of Special Populationsmentioning
confidence: 99%
“…Moreover, about 50% of T2DM patients develop chronic kidney disease (CKD) ( 8 , 9 ). Patients with CKD appear to have a higher risk of developing HCC compared to the general population ( 10 ). Some studies show that the HCC patient population overlaps highly with the CKD patient population ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Taiwan, HCC is the most common form of cancer diagnosed among dialysis patients [6]. Studies have reported that dialysis patients with hepatitis B infection, hepatitis C infection and cirrhosis, non-alcoholic fatty liver disease (NAFLD), and alcoholic liver disease are at an increased risk of developing HCC [7][8][9][10]. In fact, a changing scenario of HCC risk factors emerged in recent years, with increasing proportions of HCC risk related to non-viral metabolic liver disease.…”
Section: Introductionmentioning
confidence: 99%